Competition model characteristics of elite male sprinters - Stoyanov, H. (New Studies in Athletics, 2014)
The aim of this study was to help coaches with the planning and management of the training process for the men's 100m by studying the characteristics of the competition models of elite sprinters. Discovering the internal structure and dynamics of top performances allows the coach to select training means that develop the athlete's characteristics towards that of the top performance model. Thirty-five 100m performances, including several world records, at the IAAF World Championships in Athletics and Olympic Games were analysed. The performances were divided into three groups. The analysis of the effort distribution for the three groups indicates those elements of the race that impact the final result and thus call for development through training. The findings include that in the top performances (those below 9.86 sec), athletes reach maximal velocity within 60m and maintain their velocity better than the other two groups studied. A regression model was created to help coaches evaluate this sprint endurance capability of the athlete and predict the 100m result based on his 60m time.